2018
DOI: 10.1088/1361-6463/aac3eb
|View full text |Cite
|
Sign up to set email alerts
|

Stability and magnetic properties of SnSe monolayer doped by transition metal atom (Mn, Fe, and Co): a first-principles study

Abstract: Two dimensional (2D) tin selenium (SnSe) is an intriguing material with desired thermal and electric properties in nanoelectronics. In this paper, we carry on a density functional theory study on the stability and dilute magnetism of the 3d TM (Mn, Fe, and Co) doped 2D SnSe. Both the adsorption and substitution are in consideration here. We find that all the defects are electrically active and the cation substitutional doping (TM@Sn) is energetically favorable. The TM@Sn prefers to act as accepters and exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…In 2018, Yang et al [188] showed that the Cr/V-doped monolayer SnSe possessed an ferromagnetism (FM) ground state and could be a magnetic semiconductor with a band gap of 0.10 eV. Tang et al [189] revealed that the magnetism in cation substitutional TM doped 2D SnSe was determined by the arrangement of the TM-3d orbitals, and that the magnetic properties can be effectively modulated by the external electric field and charge doping. The magnetism in TM doped 2D SnSe was also reported by Luo et al [190] and Lu et al [191] The magnetic properties of TM doped monolayer β-SnSe [192] and δ-SnSe [193] have also been investigated.…”
Section: Ferroic Ordersmentioning
confidence: 99%
“…In 2018, Yang et al [188] showed that the Cr/V-doped monolayer SnSe possessed an ferromagnetism (FM) ground state and could be a magnetic semiconductor with a band gap of 0.10 eV. Tang et al [189] revealed that the magnetism in cation substitutional TM doped 2D SnSe was determined by the arrangement of the TM-3d orbitals, and that the magnetic properties can be effectively modulated by the external electric field and charge doping. The magnetism in TM doped 2D SnSe was also reported by Luo et al [190] and Lu et al [191] The magnetic properties of TM doped monolayer β-SnSe [192] and δ-SnSe [193] have also been investigated.…”
Section: Ferroic Ordersmentioning
confidence: 99%
“…In addition, due to the low cost, rich elements, and environmental friendliness, 2D IV-VI semiconductors have become a research hotspot in recent years. Monolayered SnSe is a fascinating 2D material due to its ideal electric and thermal properties in the field of nanoelectronics [20], which means it has promising applications in the photovoltaic industry, cut-off devices, and infrared lasers [21][22][23]. It has been reported that the adsorption behaviors of some small gas molecules on a GeS sheet [11], a SnS sheet [24], and an α-SnSe sheet [25].…”
Section: Introductionmentioning
confidence: 99%
“…The lattice constants a and b are 4.41 and 4.28 Å, respectively, in good agreement with the data in the literature. 37,38,57,58 The monolayer SnSe possesses a hinge-like structure in the x−y plane, and the x and y directions are named as the armchair direction and zigzag direction, respectively, according to their geometric configurations. The 2D SnSe composited with Mn nanowires is termed as wMn− SnSe, where w denotes the number of armchair chains in each unit cell of the composite structures (Figure 1b presents the top and side views of 6Mn−SnSe with Mn nanowires along the zigzag direction).…”
Section: Resultsmentioning
confidence: 99%